Microcrack pattern propagations and rock quality designation of Batu Caves limestone - Mohd Pauzi, Nur Irfah; Omar, Husaini; Kim Huat, Bujang; Misran, Halina; Md Yusoff, Zainuddin (Electronic Journal of Geotechnical Engineering, 2011)
Microcrack pattern of limestone with various grade of natural weathering were studied to examine the microcrack initiation and propagations in relation to Rock Quality Designation (RQD) and shear strength parameters such as shear stress and normal stress. The degree of natural weathering were determined using Schmidt hammer test and it was found that as the weathering grade increased from grade I to grade IV, the microcrack length changed from ca. 500 μm to a longer length of ca. 800 μm. The increased in microcrack length were coupled with the increased in width of the cracks as observed using Scanning Electron Microscope (SEM). Furthermore, it was suggested that the microcrack length of limestone is inversely proportional to RQD value with confidence level of 60%. However, the microcrack length of limestone was observed to be directly proportional with shear stress and normal stress with confidence level of 95% and 99% respectively.